S100B actions on glial and neuronal cells in the developing brain: an overview - Hernández-Ortega, Karina; Canul-Euan, Arturo Alejandro; Solis-Paredes, Juan Mario; Borboa-Olivares, Héctor; Reyes-Muñoz, Enrique; Estrada-Gutierrez, Guadalupe; Camacho-Arroyo, Ignacio (Frontiers in Neuroscience, 2024)
The S100B is a member of the S100 family of "E" helix-loop-"F" helix structure (EF) hand calciumbinding proteins expressed in diverse glial, selected neuronal, and various peripheral cells, exerting differential effects. In particular, this review compiles descriptions of the detection of S100B in different brain cells localized in specific regions during the development of humans, mice, and rats. Then, it summarizes S100 B's actions on the differentiation, growth, and maturation of glial and neuronal cells in humans and rodents. Particular emphasis is placed on S100B regulation of the differentiation and maturation of astrocytes, oligodendrocytes (OL), and the stimulation of dendritic development in serotoninergic and cerebellar neurons during embryogenesis. We also summarized reports that associate morphological alterations (impaired neurite outgrowth, neuronal migration, altered radial glial cell morphology) of specific neural cell groups during neurodevelopment and functional disturbances (slower rate of weight gain, impaired spatial learning) with changes in the expression of S100B caused by different conditions and stimuli as exposure to stress, ethanol, cocaine and congenital conditions such as Down´s Syndrome. Taken together, this evidence highlights the impact of the expression and early actions of S100B in astrocytes, OL, and neurons during brain development, which is reflected in the alterations in differentiation, growth, and maturation of these cells. This allows the integration of a spatiotemporal panorama of S100B actions in glial and neuronal cells in the developing brain.